Vulnerable workers and the demise of adult education in England. Issue 2 (27th October 2021) - Wallis, Emma; Nacua, Lizel; Winterton, Jonathan
Abstract : Purpose: This paper reviews changing government policy on adult education in England over the past 20 years and the funding regimes affecting adult and community learning and union-led learning, which play a major role in learning opportunities for socially excluded adults. Design/methodology/approach: A review and analysis of extant literature, informed by previous involvement in the sector and ongoing collaborations. Findings: Two decades ago, adult education in England provided a variety of learning opportunities for people who either had limited qualifications or who needed to reskill for whatever reason. Access to those opportunities has been reduced just when it is most needed. Research limitations/implications: This is a review and viewpoint paper based on experience in England, the limitations of which are discussed in the concluding section. Notwithstanding the institutional specificities of adult education in England, many of the implications are generic and have wider relevance beyond this country context. Practical implications: Economic recovery post-coronavirus (COVID) and Brexit will require more access to adult education so people can prepare for labour market re-integration. The practical implication of extending provision in adult education to support labour market integration of vulnerable workers is relevant to most countries. Originality/value: This paper takes a holistic view of adult education, with particular attention to adult and community learning and union-led learning.